Distribution Pattern of Cinnamomum tamala in Annapurna Conservation Area, Kaski, Nepal - Subedi, Mukti Ram; Timilsina, Yajna Prasad (Nepal Journal of Science and Technology, 2015)
To assess the ecological process and to find the factors responsible for pattern formation, analysis of spatial pattern of the species is of paramount importance. With a view to analyze the distribution pattern of the Cinnamomum tamala spp., this study utilized the data obtained from the phyto-sociological survey of natural vegetation carried out in Mijure Danda Village Development Committee during June and July of 2009. Nested quadrats of 10m×10m, 5m×5m, and 1m×1m were used to collect the data from tree, sapling, and seedling, respectively. Dispersion indices: variance to mean ratio (I), index of Morisita (Iä), coefficient of Green (Cx), and the k exponent of negative binomial distribution were used to identify the distribution pattern of the species. Test of significance of I, and Iäprovided the information on rejection of null hypothesis: C. tamala does not follow the random distribution. The K exponent of negative binomial distribution suggests moderate contiguous pattern, which is in line with the previous studies of vegetation elsewhere. Since this study used the cross-sectional data, monitoring of species at different temporal and spatial scale focused around various level of sampling, and accumulation of significant data on other physical elements is prescribed for future study to fill the gap of information about this species. DOI: http://dx.doi.org/njst.v15i2.12110 Nepal Journal of Science and Technology Vol. 15, No.2 (2014) 29-36